Problematic internet use among people with dentofacial deformity: a preliminary study - Kożybska, Marta; Szpyt, Justyna; Pajor, Kacper; Radlińska, Iwona; Wojtkowska, Anna; Karakiewicz, Beata (Frontiers in Psychiatry, 2025)
ObjectiveClass III malocclusion represents one type of anterior malocclusions, characterised by a longer face and a more prominent chin. Class III malocclusions are a type of malocclusion related to the relationship between the maxilla and mandible. They are often characterized by mandibular protrusion relative to the maxilla, and in some cases, features such as elongation of the lower facial third or a more prominent chin may also be present. Due to their appearance, patients experience a range of psychosocial and emotional difficulties, which have also been identified as risk factors for problematic internet use (PIU), including depression, negative body image, and lower self-esteem.MethodsA cross-sectional study was conducted and 170 fully completed questionnaires were obtained, 85 from people with Class III malocclusions aged between 18 and 42 years, and 85 from individuals without Class III malocclusions aged between 18 and 40 years.ResultsParticipants with Class III malocclusions obtained statistically significantly more PIU points than participants without Class III malocclusions (p < 0.001). Among people with Class III malocclusions 45.9% showed a high or very high risk of Internet addiction, while in the comparison group, it was only 9.4% (p < 0.001). Among participants with Class III malocclusions, there was a statistically significant, although weak, correlation between the PIU score and feeling uncomfortable when being the centre of attention (rho = 0.284; p < 0.01), and between the PIU score and concern with appearance (rho = 0.272; p < 0.05).ConclusionIndividuals with Class III malocclusion are at a much higher risk of problematic Internet use than people without the disorder. This problem especially concerns patients who feel discomfort when being the centre of attention and are more concerned about their appearance. Therefore, it seems that people suffering from disorders that cause changes in appearance should have access to extensive psychological support, including the prevention of problematic Internet use.